Compulsive ChatGPT usage, anxiety, burnout, and sleep disturbance: A serial mediation model based on stimulus-organism-response perspective - Cong Doanh Duong; Thanh Tung Dao; Trong Nghia Vu; Thi Viet Nga Ngo; Quang Yen Tran (Acta Psychologica)
The limited understanding of the detrimental repercussions stemming from the adoption of artificial intelligence, exemplified by ChatGPT, on users' mental health issues underscores the urgency of our current research endeavor. In response to this knowledge gap, our study employs the stimulus-organism-response (SOR) framework and implements a serial mediation model to probe into the impacts of compulsive ChatGPT usage on users' mental health outcomes. This model serves as a powerful analytical lens, allowing us to unravel the relationships between the stimulus (compulsive ChatGPT usage), organism (anxiety and burnout), and response (sleep disturbance). Using a cross-sectional survey design, we collected data from 2602 ChatGPT users in Vietnam via purposive sampling and utilized structural equation modeling to assess the hypothesis model. The findings confirm that compulsive ChatGPT usage directly correlates with heightened anxiety, burnout, and sleep disturbance. Moreover, compulsive usage indirectly contributes to sleep disturbance through anxiety and burnout, demonstrating a significant serial mediation effect. This expanded understanding, derived from a sizable and diverse user base, positions our research at the forefront of unraveling the intricate dynamics between AI adoption and mental well-being.